Taxifolin increased semen quality of Duroc boars by improving gut microbes and blood metabolites - Zhou, Yexun; Chen, Liang; Han, Hui; Xiong, Bohui; Zhong, Ruqing; Jiang, Yue; Liu, Lei; Sun, Haiqing; Tan, Jiajian; Cheng, Xiaowei; Schroyen, Martine; Gao, Yang; et al. (Frontiers in Microbiology, 2022)
Abstract Taxifolin (TAX), as a natural flavonoid, has attracted broad interest due to its strong anti-oxidation, anti-inflammation, anti-virus, and even anti-tumor activity. However, the effect of TAX on semen quality was unknown. The purpose of this investigation was to explore the beneficial effects of supplementing dietary TAX on boar semen quality and the underlying mechanisms. We discovered that TAX increased sperm motility significantly of Duroc boars by the elevation of the protein levels such as ZAG, PKA, CatSper and p-ERK for sperm quality. Meanwhile, TAX increased blood concentration of testosterone derivatives, antioxidants such as melatonin and betaine, unsaturated fatty acids such as DHA, and beneficial amino acids such as proline. Conversely, TAX decreased 10 different kinds of bile acids in the plasma. Moreover, TAX increased “beneficial” microbes such as Intestinimonas, Coprococcus, Butyrivibrio and Clostridium_XlVa at the Genus level. However, TAX reduced the “harmful” intestinal bacteria such as Prevotella, Howardella, Mogibacterium and Enterococcus. There were very good correlation among fecal microbes, plasma metabolites and semen parameters by the spearman correlation analysis. Therefore, the data suggest that TAX increases boar semen quality via benefiting the gut microbiota and blood metabolome. TAX may be used as dietary feed additive to increase boar semen quality in swine industry so as to demand pork consumption of people.